Defining digital joy-of-use criteria for seniors: a design approach to build motivational user experiences for older generation - Bauer, Michel (2021)
The recent increase of aging population across Europe and the rest of the globe represents one of the most radical demographic changes in the history of humankind. The increase of ageing society will have a vast effect on governments, families, individuals and companies, humans getting older has deeply modified societies, making it possible that three or more generations live together within the same environment. Due to digital environments, it is important that the needs of older generations are adequately taken into account when it comes to modern communication. In recent years, there has been a lot of research on necessary usability standards within website development for the aged generation, however a functioning usability is not the only point to consider for a successful realization of a digital product. Therefore, the objective of this thesis is to identify which criteria in terms of Joy-of-Use can help to motivate older people to use digital applications. The results should contribute to provide additional recommendations for the development of the project “Never-too-old”. The underlying research in this thesis is divided in two parts, in the first part experts in the field of ageing society have been interviewed, to get a better understanding and validate the findings within the literature review. In the second part of the study, people over the age of 60 years have been interviewed, to understand which criteria of Joy-of-Use motivates them to use digital applications. The results show that especially the criteria stimulation of the intellect, identification with the product and arousal of curiosity play an important role within the analyzed target group.